Cardiovascular disease in type 2 diabetes mellitus: progress toward personalized management - Ma, Cheng-Xu; Ma, Xiao-Ni; Guan, Cong-Hui; Li, Ying-Dong; Mauricio, Dídac; Fu, Song-Bo (Cardiovascular diabetology, 2022)
Cardiovascular diseases (CVDs) are the main cause of death among patients with type 2 diabetes mellitus (T2DM), particularly in low- and middle-income countries. To effectively prevent the development of CVDs in T2DM, considerable effort has been made to explore novel preventive approaches, individualized glycemic control and cardiovascular risk management (strict blood pressure and lipid control), together with recently developed glucose-lowering agents and lipid-lowering drugs. This review mainly addresses the important issues affecting the choice of antidiabetic agents and lipid, blood pressure and antiplatelet treatments considering the cardiovascular status of the patient. Finally, we also discuss the changes in therapy principles underlying CVDs in T2DM.